Composition and aerial biomass dynamics after burning of a grassy-woody savanna in the Pantanal wetlands - Crispim, Sandra Mara Araújo; Rodrigues, Cristina Aparecida G.; Junior, Waldomiro Barioni; Cardoso, Evaldo Luis (Pesquisa Agropecuaria Brasileira, 2000)
The purpose of this work was to evaluate composition and aerial biomass dynamics after burning of a grassy-woody savanna in the Pantanal wetlands, Brazil. During 11 months, data on species frequency, aerial biomass and soil cover were collected in an area with burning (WB) and another free of burning (FB), both not grazed. Burning reduced the frequency of the most predominant grasses and increased the number of dicotyledons and cyperaceae species. The production of total aerial biomass was lower in the WB area, despite an increase tendency that was similar in both areas. Litter production was strongly affected by burnings. After 11 months its production was approximately 25% of the production exhibited by the FB area. Soil cover was also lower in the WB and only after four months it was similar to the FB area.